PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA MASA PERALIHAN PANDEMI MENUJU ENDEMI COVID-19 - Titin Patimah; Nita Fauziah Oktaviani (Departemen Manajemen, 2023)
This research has the following objectives: 1. To determine the simultaneous effect of leadership and the work environment on work motivation during the transition from the pandemic to the Covid-19 endemic, 2. To determine the partial effect of leadership and the work environment on work motivation during the transition from the pandemic to the Covid endemic -19. Sampling in this study by taking part of the population to be 280 PNS teachers at SMP Kota Tasikmalaya. The sampling process is carried out proportionally. The research method uses a quantitative research method using a questionnaire and using a Likert scale. Data analysis techniques using validity, reliability, classical assumption tests and multiple linear regression equations were partially tested using the t test and F test with the help of SPSS software. The results of this study is leadership and work environment has a significant effect on work motivation. And leadership and work environment partially has a significant effect on work motivation. In addition, between leadership and the work environment that has the greatest influence, namely leadership.